Screening of antioxidants as stabilisers for Jatropha curcas L. oil. Issue 8 (11th June 2013) - Subroto, Erna; Manurung, Robert; Heeres, Hero Jan; Broekhuis, Antonius Augustinus
Abstract The effect of antioxidants on the oxidation stability of oils extracted from Jatropha curcas seeds was measured by the accelerated oxidation test specified in EN 14112 using commercial Rancimat 873 equipment. To find the appropriate antioxidant for jatropha oil, fourteen different antioxidants were screened at concentrations of 500 and 1000 ppm. Pyrogallol (PY) and propyl gallate (PG) significantly improved the oxidative stability of jatropha oil and PY was further studied at concentrations of 50–1000 ppm. Even at concentrations as low as 50 ppm, PY was found to fulfill the specifications set by the DIN 51605 norm for plant oil as biofuels. Mixtures of antioxidants were tested at concentrations varying between 100 and 1000 ppm, showing a synergistic effect for the combination of PY and N, N′‐di‐sec‐butyl‐p‐phenylenediamine at all concentrations and ratios tested. It further was found that the quality, i.e. the history of the oil in terms of processing, age and storage conditions, strongly affects the performance of PY as the antioxidant. PY in particular improved the oxidative stability of oxidized and highly acidic oils. PY was found to be a good antioxidant for both jatropha oil and the derived biodiesel. Practical applications: Jatropha oil is one of many potential triglyceride feedstocks suitable for the production of biofuel or other consumer products. Finding the best antioxidant for this particular resource is important since the resistance to oxidative degradation depends on the chemical structure of the triglyceride. Pyrogallol was found to be the preferred antioxidant with beneficial results found for oxidized and, as a result, highly acidic oils. The results of this study are useful for companies involved in jatropha oil‐derived products such as biodiesel, lubricants or other non‐food applications.